If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6r + -23 = -11 + 2r Reorder the terms: -23 + 6r = -11 + 2r Solving -23 + 6r = -11 + 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. -23 + 6r + -2r = -11 + 2r + -2r Combine like terms: 6r + -2r = 4r -23 + 4r = -11 + 2r + -2r Combine like terms: 2r + -2r = 0 -23 + 4r = -11 + 0 -23 + 4r = -11 Add '23' to each side of the equation. -23 + 23 + 4r = -11 + 23 Combine like terms: -23 + 23 = 0 0 + 4r = -11 + 23 4r = -11 + 23 Combine like terms: -11 + 23 = 12 4r = 12 Divide each side by '4'. r = 3 Simplifying r = 3
| 0.9z+8.25=1.5(2+2z) | | 11x^2-8x=3 | | 2x-28=-30+x | | s-8/(-8)=-1 | | V=1/3Ah | | 18/25-4/35 | | -1(x-27)+3(x+3)=9x-59 | | 24y-(y-27)=1(y-54) | | 200x^4=-800x^3+9000x^2 | | 100=-16t^2-20t+436 | | 1+4x-21x^2=0 | | 2y+7y=180 | | C=38.48+0.50x | | 2w(w+2)=0 | | 8(p-1.25)=4(2p-0.5) | | 105x^2-238x+105=0 | | x+0.5=-0.16666 | | 5+r/(-2)=-6 | | 14y^2=180 | | (2x^-3y^2)^-4/(2x^2y)^-3 | | y=-4x/1 | | y=4x/1 | | 3log(2x)+4=7 | | x^3+11x^2+18=0 | | 6n+21=57 | | sin^2x-3sinx-10=0 | | ln(9x-8)=6 | | 7x-4+6x=7x+35-7x | | 13(t-5)+5t=6(3t+3)-13 | | 36u^2=9u | | -6X+13+7X=-2 | | -.45(40)+.8X=.3(40+X) |